SAT0360 Etanar – A Etanercept Biosimilar is as Effective as Adalimumab and Infliximab in a Cohort of Real-Life of Patients with Rheumatoid Arthritis. (9th June 2015) - Santos-Moreno, P.; Saavedra-Martinez, G.; Villarreal, L.; Gomez, D.; Bello-Gualtero, J.; Giraldo, V.; Martinez, P.; Sanchez, A.; Sanchez, M.; Uribe, E.; Boon, M.
Abstract : Background: Clinical response in patients with rheumatoid arthritis (RA) using biologics is well-known. However, there is no direct comparison between biologics in cohorts of patients with RA in real-life settings, which could have implications in treatment decisions and health economics. Objectives: The aim of this study was to describe a direct comparison in effectiveness between two classical antiTNF biologics (Adalimumab, Infliximab) and one Etanercept biosimilar in patients with long-standing RA in a cohort of real-life. Methods: A descriptive cross-sectional study was performed. Were included 158 patients with at least 6 visits to rheumatologist in last 24 months in a specialized in RA center. Clinical follow-up was designed by the authors according to DAS28 as follows: every 3-5 weeks (DAS28 >5.1), every 7-9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11-13 weeks (DAS28 <3.1). Therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it; we considered this follow-up type as implementation of a T2T strategy. We divided patients in two groups: remission-low disease activity (Rem/LDA) patients and moderate-severe disease activity (MDA/SDA) patients and the aim of the study was to look at what percentage of patients who were MDA/SDA disease activity reached a low disease activity or remission. 158 patients with RA and using Adalimumab, Infliximab and Etanercept biosimilar (Etanar® CP Guojian Pharmaceutical Co Ltd, China) were involved. The Etanercept biosimilar was approved for using in Colombia since 2007. Descriptive epidemiology was done, the medians were analyzed using t-Student assuming normality for DAS28 distribution and disease activity was analyzed using Pearson's statistics. Results: 158 patients were included in this study, 125 (79.1%) women and 33 (20.9%) men. Average age was 59±10 y/o with disease duration of 11 years (0.5-47). 158 patients with diagnosis of RA using Adalimumab, Etanercept and Infliximab were involved: Adalimumab 61 (38.6%), Etanercept 25 mg 62 (39.2%), and Infliximab 35 (22.2%). At 24 months was observed an increase in percentage of patients in remission and a decrease in percentage of patients in MDA/SDA disease activity statistically significant. for Adalimumab at beginning DAS28-3.6 and 24 months later 2.6; for Etanercept biosimilar at beginning DAS28-3.6 and 24 months later 2.6 and for Infliximab at beginnng DAS28-3.6 and 24 months later 2.6. There were not statistically significant differences between analyzed biologics. On the other hand, there were fewer adverse events with Etanercept-biosimilar than Adalimumab and Infliximab; it was statistically significant. Conclusions: This study shows that the Etanercept biosimilar is as effective as 2 other traditional anti-TNF biological for disease activity control in patients with rheumatoid arthritis in a real-life setting with fewer adverse events, which could have implications in treatment decisions and health economics. On the other hand the study proves effectiveness of implementation of a T2T strategy in patients with RA. Disclosure of Interest: None declared